Beyond Compliance: Bureaucratic Innovation and Institutional Change in The Implementation of The Environmental SDG’s in Lamongan Regency - Midkholus Surur Surur (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
The implementation of the Sustainable Development Goals (SDGs) at the Indonesian local government level faces a persistent gap between formal adoption of the global framework and substantive changes in bureaucratic practices. This gap has not received an adequate theoretical explanation, especially in the context of SDGs in the environmental sector in districts with complex institutional characteristics. This research aims to develop a conceptual framework that explains the nature and depth of bureaucratic innovation in the implementation of SDGs in the environmental sector in Lamongan Regency, East Java, as an empirical reference. Using a conceptual analysis approach based on literature synthesis, this study applies Sociological Institutionalism and integrates it with the concept of institutional work and inhabited institutions. Three main findings were produced: the simultaneous working pattern of the three isomorphism mechanisms (coercive, mimetic, normative) with different intensities; the construction of a transformation-compliant continuum with four distinguishable analytical positions; as well as three theoretical propositions that can be empirically tested. The analysis shows that the dominance of coercive isomorphism encourages procedural compliance, while the movement towards substantive institutional transformation, which goes beyond compliance, requires the strengthening of normative isomorphism and the presence of institutional entrepreneurs who actively carry out institutional work. These findings contribute to the literature on SDGs localization, public sector innovation, and organizational sociology, with practical implications for environmental SDGs policy design at the local and national levels.